Functioning in Two Organisational Cultures and Organisational Commitment – A Case Study of an Outsourcing Company - Ferreras-Tascón, Maria; Golińska, Agnieszka (Acta Universitatis Lodziensis. Folia Oeconomica, 2025)
The aim of this article was to analyse the functioning of IT professionals from an outsourcing company operating simultaneously within two organisational cultures: that of their employing organisation and that of the client company, with a particular focus on identifying the key factors influencing their commitment to the employing organisation. The study was based on individual in-depth interviews conducted with ten professionals from Poland working within both their employing organisation’s and the client’s organisational cultures. The study results indicate that IT professionals interviewed were accustomed to outsourcing and functioned well in both organisational cultures. The participants declared a high level of organisational commitment, shaped mainly by development opportunities, good working conditions, and a supportive team. They particularly appreciated HR practices such as training budgets, course funding, and financial incentives. IT professionals consciously assessed both the advantages and disadvantages of the business model adopted and the variety of experiences resulting from working for both organisations. Furthermore, an additional aim of the article was to develop practical recommendations for outsourcing companies. These suggestions focus on good practices for effective team management and enhancing organisational commitment in the IT sector, which is characterised by a multicultural environment and an employee-driven market.